A design‐oriented approach for managing colored light sources in lighting design software. Issue 1 (2nd September 2022) - Rossi, Maurizio
Abstract: In the last decade, the extensive introduction of LED lighting sources has brought elements of innovation to interior lighting design in terms of color. Besides the new tunable white LED source, lighting is no longer exclusively white; indeed, colored lighting has entered the design practice thanks to the positive effects on people's health and mood. Unfortunately, this element of lighting innovation, color, cannot be computed correctly in commercial lighting design software. These computations are based on the assumption that light is only white or defined in terms of RGB triplets in the relative digital color space of computer graphics, which does not have a physically correct relationship with the actual spectral power distribution (SPD) of luminaires. In this paper, attention is focused on a practical design‐oriented approach for describing luminaires in lighting design software that also considers the real SPD and the luminous intensity distribution. The focus is on information available to lighting designers who do not have a laboratory to measure light sources and luminaires. This information could be available in online datasheets or as a Cartesian graph from luminaires and light sources manufacturers. Following this approach, a set of functions is proposed that can be easily implemented in lighting design software to improve light sources' color management and allow lighting designers to add SPD data to luminaires.